1984
DOI: 10.1007/bf00687615
|View full text |Cite
|
Sign up to set email alerts
|

Hemiplegic atrophy

Abstract: Anterior tibial muscle biopsies of the hemiplegic side of 16 patients with a cerebrovascular accident in the middle cerebral artery region were analyzed qualitatively and quantitatively by enzyme histochemistry and electron microscopy. Patients grouped according to the time lapsed as from the occurrence of the accident (1-17 months) demonstrated a progressive decrease in the fiber diameter and changes in fiber type distribution with predominant type II atrophy and type I predominance. Nuclear internalization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…The changes in motor unit behavior in both the upper and lower limbs may result from altered physiology such as decreased central drive (e.g., Nielsen et al, 2008; Klein et al, 2013) but also from altered anatomy. Within muscles there may be a reduction in the number of functioning motor units (Hara et al, 2000, 2004; Arasaki et al, 2006; Lukács et al, 2008); and muscle fiber atrophy (Scelsi et al, 1984; Slager et al, 1985) associated with muscle disuse (Ramsay et al, 2011). Perhaps the least understood change in muscles after stroke, and one that will affect the behavior of individual motor units, is the pattern of denervation and reinnervation that is thought to underpin changes in muscle phenotype (for review see Hafer-Macko et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in motor unit behavior in both the upper and lower limbs may result from altered physiology such as decreased central drive (e.g., Nielsen et al, 2008; Klein et al, 2013) but also from altered anatomy. Within muscles there may be a reduction in the number of functioning motor units (Hara et al, 2000, 2004; Arasaki et al, 2006; Lukács et al, 2008); and muscle fiber atrophy (Scelsi et al, 1984; Slager et al, 1985) associated with muscle disuse (Ramsay et al, 2011). Perhaps the least understood change in muscles after stroke, and one that will affect the behavior of individual motor units, is the pattern of denervation and reinnervation that is thought to underpin changes in muscle phenotype (for review see Hafer-Macko et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Achilles tendon properties have been shown to change between the paretic and nonparetic sides [20], and it is still unclear whether the properties of the tibialis anterior tendon change following stroke. Finally, we did not look at changes in muscle fiber type although [30] performed histological biopsies of the tibialis anterior and found that type II muscle fibers reduce in number and diameter, with a predominant shift towards type I fibers. This change in fiber type ratio, if consistent for chronic stroke survivors, may be indicative of activation failure or disuse.…”
Section: Discussionmentioning
confidence: 99%
“…After a stroke the number of Type II fibers progressively decrease, resulting in a loss of skeletal muscle cross-sectional area. 11, 31, 32 Similar to age-related muscle atrophy, after stroke there is a progressive decrease in muscle fiber size bilaterally, with greater decreases on the more involved side. 32 Stroke-induced muscle fiber reductions lead to a decrease in muscle cross-sectional area.…”
Section: Muscular Changesmentioning
confidence: 99%
“…11, 31, 32 Similar to age-related muscle atrophy, after stroke there is a progressive decrease in muscle fiber size bilaterally, with greater decreases on the more involved side. 32 Stroke-induced muscle fiber reductions lead to a decrease in muscle cross-sectional area. In individuals post-stroke, diminished force production and contraction speed secondary to muscle atrophy may be observed as difficulty with sit to stand transfers, 33, 34 limitations in stair negotiation, 35 and impaired balance on compliant surfaces.…”
Section: Muscular Changesmentioning
confidence: 99%